Association Between Initiation, Intensity, and Cessation of Smoking and Mortality Risk in Patients With Cardiovascular Disease: A Cohort Study - Wang, Jiang-lin; Yin, Wen-jun; Zhou, Ling-yun; Wang, Ya-feng; Zuo, Xiao-cong (Frontiers in Cardiovascular Medicine, 2021)
Objectives: To examine the effect of smoking status, smoking intensity, duration of smoking cessation and age of smoking initiation on the risk of all-cause and cause-specific mortality among cardiovascular disease (CVD) patients. Participants: 66190 CVD participants ≥ 18 years of age who were interviewed between 1997 and 2013 in the National Health Interview Survey (NHIS) linked to the National Death Index (NDI) through December 31, 2015. Outcome measures: The primary outcome was all-cause mortality and the secondary outcome was cause-specific mortality including CVD mortality and cancer mortality. Results: During the mean follow-up of 8.1 years, we documented 22518 deaths (including 6473 CVD deaths and 4050 cancer deaths). In the overall CVD population, former and current smokers had higher risk of all-cause (Former smokers: hazard ratios (HRs), 1.26; 95% confidence interval (CI), 1.21-1.31, P＜0.001; Current smokers: HRs, 1.96; 95%CI, 1.86-2.07, P＜0.001), CVD (Former smokers: HRs, 1.12; 95%CI, 1.05-1.21, P=0.001; Current smokers: HRs, 1.80; 95%CI, 1.64-1.97, P＜0.001) and cancer mortality (Former smokers: HRs, 1.49; 95%CI, 1.35-1.64, P＜0.001; Current smokers: HRs, 2.78; 95%CI, 2.49-3.09, P＜0.001) than never smokers. Furthermore, similar results were observed when the study subjects were stratified according to the type of CVD. Among current smokers, the risk for cancer mortality increased as the daily number of cigarettes increased, regardless of the specific type of CVD. However, the association of the risk for all-cause and CVD mortality with smoking intensity did not present a dose-response relationship. In participants with angina pectoris or stroke, smoking intensity was inversely associated with deaths from CVD. In addition, the risk for all-cause, CVD and cancer mortality declined as years of smoking cessation increased. Finally, the relative risk of all-cause mortality was not significantly different in individuals with a younger age of smoking initiation. Conclusions: CVD patients who are smokers have an increased risk of all-cause, CVD and cancer mortality, and the risk decreases significantly after quitting smoking. These data further provide strong evidence that supports the recommendation to quit smoking for the prevention of premature deaths among individuals with CVD.